Power relations within the second-hand clothing industry touching down in Ghana - Verena Mayer (Südwind-Verlag, 2024)
This Master Thesis offers valuable insights for academic and policy debates on the socio-economic impacts of the global second-hand clothing trade and the inherent inequalities within this industry. Verena Mayer's work stands out for its theoretical engagement and detailed empirical investigation, making a significant contribution to understanding a largely invisible segment of the global garment industry.
Keywords: 330